2018
DOI: 10.2528/pierl17102001
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Coupling for a WPT System Including Dielectric/Magnetic Materials

Abstract: Abstract-Dielectric or magnetic materials introduced in a wireless power transfer (WPT) system affect the properties of WPT. This paper quantitatively studies the coupling between the transmitting and receiving elements for a WPT system including either dielectric or magnetic materials. The transmitting and receiving elements are open spirals and solenoid coils which are usually used in WPT systems. The analysis method is the perturbation method which can calculate the total coupling coefficient k, the electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In our study, E and H fields are obtained by a commercial simulation software HFSS @ ; k, k m and k e are calculated by a program made by ourselves according to Equations (2), (3) and (4). Our previous studies have proved that the overlap integral method is useful in the coupling analysis between electromagnetic devices [16][17][18][19][20].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, E and H fields are obtained by a commercial simulation software HFSS @ ; k, k m and k e are calculated by a program made by ourselves according to Equations (2), (3) and (4). Our previous studies have proved that the overlap integral method is useful in the coupling analysis between electromagnetic devices [16][17][18][19][20].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Our previous studies also presented some results on the electromagnetic coupling [16,17]. Some of them focused on the coupling in WPT systems [18][19][20]. In a WPT system, coupling between the resonators depends on many factors such as structure of resonator, distance and alignment between the resonators and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…e purpose of using a dielectric resonator is to reduce the ohmic loss in the conventional resonator. Studies in the field of material sciences [30,31] have shown that dielectric material can increase the Q factor through the permittivity characteristic exhibited in the dielectric material. Previous review paper published in 2010 [31,32] presented an extensive review on dielectric material and design.…”
Section: Introductionmentioning
confidence: 99%